Anatase/TiO2-B hybrid microspheres constructed from ultrathin nanosheets: facile synthesis and application for fast lithium ion storage. Issue 41 (30th September 2015) - Cui, Peng; Xie, Bixia; Li, Xiaodan; Li, Meicheng; Li, Yaoyao; Wang, Yu; Liu, Zhuohai; Liu, Xin; Huang, Jing; Song, Dandan; Mbengue, Joseph Michel
Abstract : Anatase/TiO2 -B hybrids are considered to be promising anode materials for lithium ion storage. Here, a modified synthesis process for the fabrication of anatase/TiO2 -B hybrid TiO2 spheres is proposed. Abstract : Anatase/TiO2 -B hybrids are considered to be promising anode materials for lithium ion storage. Here, a modified synthesis process for the fabrication of anatase/TiO2 -B hybrid TiO2 spheres is proposed. Compared to the conventional two-step method employing strong base and acid solutions with titanate as the intermediate, the modified process proposed here employs a one-step reaction which is more facile and moderate. The as-prepared anatase/TiO2 -B hybrid TiO2 spheres are assembled from ultrathin anatase TiO2 nanosheets embedded with TiO2 -B nanodomains, which take the advantages of both the anatase and TiO2 -B phases, possessing a large surface area and a hybrid crystalline structure, which are beneficial for fast diffusion and reversible storage of the lithium ions. Therefore, the anodes with the anatase/TiO2 -B hybrid TiO2 spheres have a capacity of 101 mA h g −1 even at a current density of 20C and good cycling stability. This work provides a facile process for the fabrication of TiO2 nanostructures with the TiO2 -B phase, which also implies the potential application of anatase/TiO2 -B hybrid spheres in many fields including lithium ion batteries and other electrochemical technologies.